Father’s strength inspires Wan Nur Ainna, receives Yayasan Pahang Excellence Prize - Siti Nurfarmy, Ibrahim (2022)
PAYA BESAR, 5 November 2022 – The loss of her beloved mother, Maisarah Hilal Mohd Alwi, in the final year of diploma study due to stroke, made Wan Nur Ainna Amirah Wan Zulkifli bounced back to pursue her bachelor’s degree.